PERAN MASYARAKAT DALAM MELINDUNGI KEPUNAHAN BURUNG CENDERAWASIH DIKAMPUNG BARAWAI DISTRIK RAIMBAWI KABUPATEN KEPULAUAN YAPEN - , Semuel Numberi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bird of paradise (Paradisea spp) is a species endemic to Papua, especially in Kampung Barawai Yapen Islands District, that does not exist anywhere in the world, keunikanya make this bird called a bird paradise. Mengakibatkan high potential illegal hunting mengurangi natural populations, due to forest exploitation and conservation of PT Kodeco leh. The above problems by forming Dorei Jaya Group, a group which acts to curb poaching and illegal logging. This study aimed to determine the community's role in protecting the extinction of birds of paradise in the village Barawai, therefore this study was conducted in the Barawai Village Yapen Islands Regency, held for 4 months. This study relies on qualitative paradigm, where the required data extracted by way of interviews with key infrman. Key informant determined that as many as 12 people from three groups: the village officials, and community groups Barawai doreri jaya. To describe the community's role in protecting the birds of paradise from extinction, then performed a descriptive analysis of data, and displayed in the form of informant statements are supported by documentation in the form of drawings and photographs. The analysis showed that, in the village of Barawai quite a role in preserving our environment and habitat of birds of paradise. doreri the glorious role in terms of (1), the socialization of the importance of conservation of birds of paradise to the community, (2), urged the government to immediately passed a law to protect conservation areas and mnyelamatkan barawai, (3) coordinating, monitoring and reporting on violations that occur . There are several factors that hamper efforts to identify, birds of paradise and habitat preservation. Factors include (1) the high demand of children's education to a higher level (2) fence of the city of paradise bird of paradise is still looking to be used as a souvenir, (3), local governments seem slow to introduce legislation that could save populations of paradise.